Effects of Tianshu Capsule on Spontaneously Hypertensive Rats as Revealed by 1H-NMR-Based Metabolic Profiling - Gao, Jian; Wang, Tieshan; Wang, Chao; Wang, Shuai; Wang, Wei; Ma, Di; Li, Yongbiao; Zhao, Haibin; Chen, Jianxin (Frontiers in Pharmacology, 2019)
Hypertension is one of the most common cardiovascular diseases, resulting in serious complications, such as cardiovascular damage and chronic kidney disease. Tianshu capsule (TSC), composed of Chuanxiong (Ligusticum chuanxiong Hort) and Tianma (Gastrodiaelata Blume), has been widely used to treat the blood stasis type of headache and migraine in clinic. Results of previous study showed its antihypertensive effects, but the underlying mechanisms were still unclear. The purpose of this study was to evaluate the antihypertensive effect of TSC on spontaneously hypertensive rats by 1H NMR-based metabonomics and enzyme-linked immunosorbent assay (ELIAS), explore potential biomarkers and targets, and probe into the potential mechanism of TSC on antihypertensive treatment. The results showed that TSC could decrease the product of oxidative stress (MDA) and enhance the activities of SOD and GSH-Px, down-regulate the expression of enzymes (LDHA, PKM2 and HK2) related to glycolysis, and perturb a series of amino acids (isoleucine, alanine, asparagine, citrate, etc.) levels and pathways. Multivariate statistical analyses showed remarkable changes in some endogenous metabolites after administrating TSC relating to oxidative stress, amino acid metabolism and energy metabolism disturbances. Some enzymes (alanine-glyoxylate aminotransferase-2, tyrosine hydroxylase, dopa decarboxylase, etc.) related to metabolic biomarkers were predicted as the potential targets of TSC treatment on SHRs. The discoveries are helpful to understand the antihypertensive mechanism of TSC and provide a theoretical evidence for its future research, development and clinical use.